WRKY36–PIL15 Transcription Factor Complex Negatively Regulates Sheath Blight Resistance and Seed Development in Rice - Siting Wang; Qian Sun; Shuo Yang; Huan Chen; Depeng Yuan; Changxi Gan; Haixia Chen; Yongxi Zhi; Hongyao Zhu; Yue Gao; Xiaofeng Zhu; Yuanhu Xuan (Plants)
Sheath blight (ShB) causes severe yield loss in rice. Previously, we demonstrated that the sugar will eventually be exported and the transporter 11 (SWEET11) mutation significantly improved rice resistance to ShB, but it caused severe defects in seed development. The present study found that WRKY36 and PIL15 directly activate SWEET11 to negatively regulate ShB. Interestingly, WRKY36 interacted with PIL15, WRKY36 and PIL15 directly activates miR530 to negatively regulate seed development. WRKY36 interacted with a key BR signaling transcription factor WRKY53. AOS2 is an effector protein from Rhizoctonia solani (R. solani) that interacts with WRKY53. Interestingly, AOS2 also interacts with WRKY36 and PIL15 to activate SWEET11 for sugar nutrition for R. solani. These data collectively suggest that WRKY36–PIL15 negatively regulates ShB resistance and seed development via the activation of SWEET11 and miR530, respectively. In addition, WRKY36 and PIL15 are the partners of the effector protein AOS2 by which R. solani hijacks sugar nutrition from rice.